The Effect of Depreciated Exchange Upon Merchandise Movements - Li., Choh-Ming (Quarterly Journal of Economics, 1935)
Journal Article The Effect of Depreciated Exchange Upon Merchandise Movements Get access Choh-Ming Li Choh-Ming Li Berkeley, Calif. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 49, Issue 3, May 1935, Pages 495–502, https://doi.org/10.2307/1883865 Published: 01 May 1935